The Canadian and British Models of Internal Control - Babuśka, Ewa W. (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The paper presents the next installment of well-known worldwide models of internal control including the Canadian model CoCo and the British models: Cadbury’s and Turnbull’s, all of which have grown out of the best practices of corporate governance. It also describes the standards which contributed to the creation of these models, and their main features. The paper goes on to explain their importance to these organisations, their auditors and others, and indicates the scope of their application in Poland and throughout the world.